2017
DOI: 10.1093/gbe/evx008
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Evolutionary History of Powdery Mildew Lineages (Blumeria graminis) at Different Evolutionary Time Scales with NGS Data

Abstract: Blumeria graminis (Ascomycota) includes fungal pathogens that infect numerous grasses and cereals. Despite its economic impact on agriculture and its scientific importance in plant–pathogen interaction studies, the evolution of different lineages with different host ranges is poorly understood. Moreover, the taxonomy of grass powdery mildew is rather exceptional: there is only one described species (B. graminis) subdivided in different formae speciales (ff.spp.), which are defined by their host range. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
2
35
1
Order By: Relevance
“…It was observed that different processes shaped the diversification of B. graminis, including co-evolution with the host species for some of the ff. spp., host jumps, host range expansions, lateral gene flow and fast radiation (Menardo et al, 2017). Arguably, as highly adapted and obligate biotrophic pathogens, powdery mildews underwent many host species-specific adaptations, which are perhaps not or less required for saprophytes and facultative and broad host range pathogens such as Verticillium species.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that different processes shaped the diversification of B. graminis, including co-evolution with the host species for some of the ff. spp., host jumps, host range expansions, lateral gene flow and fast radiation (Menardo et al, 2017). Arguably, as highly adapted and obligate biotrophic pathogens, powdery mildews underwent many host species-specific adaptations, which are perhaps not or less required for saprophytes and facultative and broad host range pathogens such as Verticillium species.…”
Section: Discussionmentioning
confidence: 99%
“…was reconstructed. It was observed that different processes shaped the diversification of B. graminis , including co-evolution with the host species for some of the ff.spp ., host jumps, host range expansions, lateral gene flow and fast radiation (Menardo et al, 2017). Arguably, as highly adapted and obligate biotrophic pathogens, powdery mildews underwent many host species–specific adaptations, which are perhaps not or less required for saprophytes and facultative and broad host range pathogens such as Verticillium species.…”
Section: Discussionmentioning
confidence: 99%
“…fungi have co-evolved with their hosts, leading to host specialization. Yet, there are exceptions where possible host jumps or host range expansions might have occurred [ 17 ]. Additionally, while the majority of grass PM fungi are monophylogenetic, there may be exceptions; for example, there are different B. graminis isolates affecting Dactylis glomerata , and therefore B. g. f.sp.…”
Section: Introductionmentioning
confidence: 99%